Time-Motion Analysis of Taekwondo Matches in the Tokyo 2020 Olympic Games - Herrera-Valenzuela, T (Edizioni Minerva Medica, 2023)
BACKGROUND: The aim of the present study was to determine the time-motion structure of high-level taekwondo matches during the Tokyo 2020 Olympic Games in relation to sex, match outcome, weight category and match round. METHODS: Overall, 7007 actions were recorded during the analysis of 134 performances (67 rounds of 24 matches: four rounds of 16, eight quarterfinals, eight semifinals and four finals) in male and female flyweight (≤58 kg and ≤49 kg, respectively), and heavyweight categories (≥80 kg and ≥67 kg, respectively). The attack time (AT), number of AT (AN), skipping time (ST) and pause time (PT) were registered. RESULTS: The AT/ST ratio was ~1:1.5. Male athletes performed significantly longer (P<0.001) sum PT than female athletes. Flyweight athletes differed significantly from their heavyweight counterparts by having longer (P<0.001) average and sum AT, greater (P<0.001) AN, higher (P<0.001) AT/ST ratio, shorter (P<0.001) average and sum ST, and lower (P<0.01) (AT+ST)/PT ratio. Rounds 2 and 3 had average PT significantly longer (P<0.01) than round 1. Round 3 had sum PT longer (P<0.001) and (AT+ST)/PT ratio lower than in round 1. CONCLUSIONS: The rule changes and the implementation of the electronic score recording system had a major impact on the time-motion structure of combat by generating a considerably higher AT/ST ratio than in the past. The comparisons indicated that the structure of the combat is modulated by weight category and phase of the combat. In practice, coaches could develop sport-specific high-intensity interval training using the time-motion indexes of the present study as guidelines. © 2023 EDIZIONI MINERVA MEDICA.